Generation of mode-locked erbium-doped fiber laser using MoSe2as saturable absorber - Ahmad, Harith; Aidit, S.N.; Hassan, N.A.; Ismail, Mohammad Faizal; Tiu, Zian Cheak (International Society for Optical Engineering (SPIE), 2016)
Mode-locked generation of erbium-doped fiber laser (EDFL) with MoSe2 thin film as saturable absorber is practically demonstrated. Bulk MoSe2 is exfoliated into few-layer MoSe2, which is achieved based on the liquid phase exfoliation technique. The few-layer MoSe2 is mixed with polyvinyl alcohol to become a thin film. Mode-locked occurs between pump powers of 65 and 218 mW. The mode-locked is operated at fundamental frequency of 8.8 MHz, and the spectrum is centered at 1560 nm. The SNR of mode-locked EDFL is more than 50 dB. At pump power of 218 mW, 91.3 pJ of pulse energy is achieved.